Interactions of conjugate vaccines and co-administered vaccines. Issue 1 (2nd January 2016) - Findlow, H; Borrow, R
Abstract : Conjugate vaccines play an important role in the prevention of infectious diseases such as those caused by the bacteria Haemophilus influenzae (Hi) type b (Hib), Neisseria meningitidis, and Streptococcus pneumoniae . Vaccines developed against these 3 pathogens utilize 3 main carrier proteins, non-toxic mutant of diphtheria toxin (CRM197 ), diphtheria toxoid (DT) and tetanus toxoid (TT). Current pediatric immunisation schedules include the administration of several vaccines simultaneously, therefore increasing the potential for immune interference (both positively and negatively) to the antigens administered. Knowledge of vaccine interactions is principally derived from clinical trials, these are reviewed here to explore immune interference which may result of from carrier-specific T-cell helper interactions, bystander interference and carrier induced epitopic suppression.